Evaluation of Working Environment by Clinical Nurses According to Healthy Working Environment Standards - Duru Yapıcı; Havva Arslan Yürümezoğlu (Dokuz Eylul University, 2021)
Background: The fact that quality health care and positive patient outcomes depend largely on good nursing care reveals the importance of improving the working environment of nurses. Objective: This study was conducted to investigate the extent to which the healthy working environment standards developed for nurses in Turkey were implemented in healthcare institutions and the perception of nurses concerning the importance and priority of main standards in creating a healthy working environment. Methods: The sample of the study consisted of 550 clinical nurses providing direct patient care in the surgical, internal medicine and intensive care units of three education research hospitals affiliated with the Ministry of Health in Izmir. A total of 309 nurses, who accepted to participate in the study and had worked in their current institution for at least one year, were included in the sample. The Individual and Work Characteristics Form and three forms prepared by the researchers taking into account the healthy work environment standards were used as data collection tools. Data were evaluated by descriptive statistics, non-parametric one-way analysis of variance, and the Mann-Whitney U test with the Bonferroni correction using SPSS v. 22.0. Written permission was obtained from the hospitals where the research was to be conducted, and the ethics committee of the university approved the study. Results: While the implementation of all of the standards had an average of 2.07 (0.49), the main standard of "Effective Management and Leadership" had the lowest average at 1.76 (0.60) and "Team Collaboration, Communication, Appreciation and Recognition" had an average of 2.27 (0.63). "Nurse Workload" was considered to be the most important Standard by 80.3% of the nurses and most prioritized by 70.3%. It was staed that the main standard of "Suitable Physical Conditions and Adequate Tools-Equipment" was implemented at a lower level in intensive care units. Conclusion: The results of this study showed that the clinical nurses considered that all the standards of healthy working environment were implemented at a low to moderate level in their institutions.